Chemical and biological-based isoprene production: Green metrics - Morais, Ana Rita C. (2014)
Green metrics is a methodology which allows the greenness of either new or already existing processesto be assessed. This paper is a part of a special issue devoted to green metrics in which this methodologyis applied to different processes to assess bio and petrochemical routes. In this work, green metrics wereused as a tool to validate and compare the petrochemical and biological processes of isoprene production.The Sumitomo process has been selected for this comparison as it is beneficial because of it using lessexpensive C1components as well as the fact that it has lower investment costs for a single-step process. The production of isoprene through a modified Escherichia coli bacterial process has been selected forcomparison with the fossil pathway. The green metrics evaluation was performed for both processes toproduce isoprene and to target 50,000 tonnes of isoprene yearly. Although, the calculated costs for the bio-isoprene are slightly higher than the actual market price ofits fossil counterpart, the results obtained reveal that the bacteria-based isoprene production is able to substitute the petrochemical process, with material and energy efficiency. This conclusion has also beenproved by the increasing number of industrial interest in bioisoprene. The challenge comes from the landuse needed for the production of a carbon source which might be solved by the use of waste and residueswhich are rich in carbohydrates or lignocellulosic biomass which can be converted to simple sugars.